KAJAOLALIDDONG, THE INTELLECTUAL OF BUGIS BONE : From The Historical Perspective - H. Muhammad Bahar Akkase Teng (International Journal of Malay-Nusantara Studies, 2018)
Kajaolaliddong was well known as a scholar and advisor to the King of Bone in term life mainly related to basic values of state (kingdom), law, and/or political culture. The thoughts of Kajaolaliddong cover the aspects of customs, justice, jurisprudence, and complete governmental systems. Kajaolaliddong was an ambassador to assist the King in overcoming the problems which occurred with the neighboring kingdoms. Besides, this appointment aimed to grow and develop the Kingdom of Bone. The methods used were the library research referring to the ancients documents, such as lontaraq (Buginese ancient manuscript), oral and previous studies. The study shows that the basic pattern called pangadereng (customs) later becomes references of the King and other officials in their activities. The main narrations of Kajaolaliddong thoughts were lempue nasibawai tau (honesty and religiosity), ada tongeng nasibawa tike (true words with vigilance), siri nasibawai getting (shame or self esteem with determination), awaraningeng nasibawai nyameng kininnawa (courage with love), appesona ri Dewata seuwwae (surrender to One God). Of these five components, Kajaolaliddong thoughts emphasized three major components, namely honesty, intelligence, and courage.